Days spent in acute care hospitals at the end of life of cancer patients in four Swiss cantons: a retrospective database study (SAKK 89/09). (9th February 2016) - Matter‐Walstra, K.W.; Achermann, R.; Rapold, R.; Klingbiel, D.; Bordoni, A.; Dehler, S.; Konzelmann, I.; Mousavi, M.; Clough‐Gorr, K.M.; Szucs, T.; Schwenkglenks, M.; Pestalozzi, B.C.
Abstract : Number of days spent in acute hospitals (DAH) at the end of life is regarded as an important care quality indicator for cancer patients. We analysed DAH during 90 days prior to death in patients from four Swiss cantons. Claims data from an insurance provider with about 20% market share and patient record review identified 2086 patients as dying of cancer. We calculated total DAH per patient. Multivariable generalised linear modelling served to evaluate potential explanatory variables. Mean DAH was 26 days. In the multivariable model, using complementary and alternative medicine (DAH = 33.9; +8.8 days compared to non‐users) and canton of residence (for patient receiving anti‐cancer therapy, Zürich DAH = 22.8 versus Basel DAH = 31.4; for other patients, Valais DAH = 22.7 versus Ticino DAH = 33.7) had the strongest influence. Age at death and days spent in other institutions were additional significant predictors. DAH during the last 90 days of life of cancer patients from four Swiss cantons is high compared to most other countries. Several factors influence DAH. Resulting differences are likely to have financial impact, as DAH is a major cost driver for end‐of‐life care. Whether they are supply‐ or demand‐driven and whether patients would prefer fewer days in hospital remains to be established.